Financing tourist activity - Vujović Slavoljub; Vukosavljević Danijela; Bjeljac Željko (Zbornik Radova: Geografski institut "Jovan Cvijić", 2014)
This paper researches which of the possible financing models (self-financing, loan, mutual fund, issuing securities and leasing) is the most convenient for tourism financing on the grounds of opinions and views of student population. Taking into account that future social and economic development depends on student population, that in every society intellectual endeavor (science and art) exists ever since man exists, that the overall progress of mankind is based on the great intellectual endeavor of former civilizations, as well as the fact that Western Serbia has remarkable natural and anthropogenic characteristics suitable for valorization for the purpose of tourism development, the research questions were formulated and the research was performed. The methods used were: analysis, correlation, deduction and induction. Field research has been of the primary importance and it was based on questionnaires, interviews and in-depth interview. [Projekat Ministarstva nauke Republike Srbije, br. 46001 i br. 47007]